FUTURE FIGURATIVE ART TO THEIR TEACHERS LANDSCAPE COMPOSITION TO COMPOSE AND TO DESCRIBE TO TEACH CREATIVE COMPETENCIES DEVELOP METHODOLOGY - Bahriyev Ilhomjon Saidazimovich (Bright Mind Publishing, 2025)
This article " Future figurative art to their teachers landscape composition to compose and to describe to teach creative competencies develop methodology " topic deep analysis It does. It has color science. and fundamental scientific composition the basics, as well as their modern artistic and pedagogical to education integration to do technologies seeing is released. Article art his work foundation in the process of composition central place, its ideological-artistic the essence illuminates. Pedagogical approaches, including Article future art their teachers aesthetic and composition in terms of literate, scientific and practical to knowledge has experts as preparation importance emphasizes.
Keywords: Color theory, Composition, Creativity, Competence, Pedagogical Education, Visual Perception, Perspective, Practical training, artistic work, Creative thinking.